The Traditional Practice of Childbirth of the Nuaulu Tribe in Seram Island, Indonesia - Sri Eny Setyowati (Universiti Kebangsaan Malaysia, 2015)
Introduction Maluku is known as an archipelagic province in Indonesia. One of its island, Seram Island, has a local tribe called Nualu’s. This tribe has a unique yet peculiar traditional practice for pregnant women. This practice is called the pregnancy in seclusion, where a Nuaulu’s pregnant woman is secluded or concealed in the small house called Posuno for 40 days prior to giving birth. Methods Two research methods are applied: qualitative and quantitative approach. The quantitative method used explanatory research with cross section approach. Within this method, questionnaire was used for data collection in order to obtain some information about respondents’ characteristics, attitude, and perceptions towards practice of pregnancy in seclusion. The sample was taken from the population of all Nuaulu’s mothers with under 3-year-old child. Out of 126 all Nuaulu’s women who had experience of being secluded in Posuno, 68 respondents participated in this research. On the other hand, qualitative method was used as a way to validate the finding from the quantitative part. This was done by conducting in depth interview with 10 persons. Results Most members of Nuaulu tribe have a “high perception” towards practice of pregnancy in seclusion, meaning that they interpret the practice as a good practice that benefit them in someway or another. In addition, there is no statistical correlation between Nuaulu’s perception and Nuaulu’s tradition in regard to pregnancy in seclusion. Conclusion The majority of Nuaulu’s women have a perception that giving birth in Posuno is better than in public healthcare. Finally, Communication, Information, and Education are needed for traditional leader and local witchdoctor in order to enhance their knowledge about a proper way giving birth according to medical recommendation.